Smarter faster better : the transformative power of real productivity - Duhigg, Charles (New York : Random House, 2017)
'At the core of [this book] are eight key concepts--from motivation and goal setting to focus and decision making--that explain why some people and companies get so much done. Drawing on the latest findings in neuroscience, psychology, and behavioral economics--as well as the experiences of CEOs, educational reformers, four-star generals, FBI agents, airplane pilots, and Broadway songwriters--this ... book explains that the most productive people, companies, and organizations don't merely act differently'--Dust jacket flap.
Introduction--Motivation--Teams--Focus--Goal setting--Managing others--Decision making--Innovation--Absorbing data.
Includes bibliographical references and index.
Keywords: Performance -- Psychological aspects; Work -- Psychological aspects; Mental efficiency; Motivation (Psychology); Decision making; Success; Achievement; Decision Making; Intelligence; Motivation; Work Performance